Coherence and Coupling Functions Reveal Microvascular Impairment in Treated Hypertension - Ticcinelli, Valentina; Stankovski, Tomislav; Iatsenko, Dmytro; Bernjak, Alan; Bradbury, Adam E.; Gallagher, Andrew R.; Clarkson, Peter B. M.; McClintock, Peter V. E.; Stefanovska, Aneta (Frontiers in Physiology, 2017)
The complex interactions that give rise to heart rate variability (HRV) involve coupled physiological oscillators operating over a wide range of different frequencies and length-scales. Based on the premise that interactions are key to the functioning of complex systems, the time-dependent deterministic coupling parameters underlying cardiac, respiratory and vascular regulation have been investigated at both the central and microvascular levels. Hypertension was considered as an example of a globally altered state of the complex dynamics of the cardiovascular system. Its effects were established through analysis of simultaneous recordings of the electrocardiogram, respiratory effort, and microvascular blood flow (by laser Doppler flowmetry). The signals were analysed by methods developed to capture time-dependent dynamics, including the wavelet transform, wavelet-based phase coherence, nonlinear mode decomposition and dynamical Bayesian inference, all of which can encompass the inherent frequency and coupling variability of living systems. Phases of oscillatory modes corresponding to the cardiac (around 1.0 Hz), respiratory (around 0.25 Hz) and vascular myogenic activities (around 0.1 Hz) were extracted and combined into two coupled networks describing the central and peripheral systems respectively. The corresponding spectral powers and coupling functions were computed. The same measurements and analyses were performed for three groups of subjects: healthy young (Y group, 24.4+/-3.4 y), healthy aged (A group, 71.1+/-6.6 y), and aged treated hypertensive patients (ATH group, 70.3+/-6.7 y). It was established that the degree of coherence between low-frequency oscillations near 0.1 Hz in blood flow and in HRV time series differs markedly between the groups, declining with age and nearly disappearing in treated hypertension. Comparing the two healthy groups it was found that the couplings to the cardiac rhythm from both respiration and vascular myogenic activity decrease significantly in aging. Comparing the data from A and ATH groups it was found that the coupling from the vascular myogenic activity is significantly weaker in treated hypertension subjects, implying that the mechanisms of microcirculation are not completely restored by current anti-hypertension medications.